2023
DOI: 10.1039/d2sc06597e
|View full text |Cite
|
Sign up to set email alerts
|

Improved production of class I lanthipeptides in Escherichia coli

Abstract: Lanthipeptides are ribosomally synthesised and post-translationally modified peptides containing lanthionine (Lan) and methyllanthionine (MeLan) residues that are formed by dehydration of Ser/Thr residues followed by conjugate addition of Cys to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…S2A). 16 In the current version, this platform includes a pETDuet plasmid that encodes a His-tagged blauticin leader and core sequence. The blauticin leader sequence is recognized by blauticin-specific LanB and LanC ( bpcB and bpcC gene, respectively) encoded in the pCDFDuet plasmid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2A). 16 In the current version, this platform includes a pETDuet plasmid that encodes a His-tagged blauticin leader and core sequence. The blauticin leader sequence is recognized by blauticin-specific LanB and LanC ( bpcB and bpcC gene, respectively) encoded in the pCDFDuet plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Using this information, an improved production platform has been established for facile expression and production of class I lanthipeptides. 16 Blauticin, a class I lantibiotic produced by the gut commensal bacteria Blautia producta SCSK (BPSCSK), exerts colonization resistance and clearance of Vancomycin-resistant Enterococci (VRE) in vivo. 17 A previous study showed that the in vivo VRE colonization in colon was inhibited by BPSCSK but not by Lactococcus lactis, the producing strain of the well-studied class I lantibiotic nisin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione (GSH) adducts to dehydroamino acids (Dha/Dhb) have been observed previously during heterologous production of lanthipeptides in E. coli. [59][60][61][62] LanC-like proteins (LanCL) have been shown to add GSH to peptides in mammalian cells, and indeed in vitro LanCL also adds GSH to CylLL. 63 To determine the location of the GSH adduct produced in HEK293 cells, a chymotrypsin digest was performed followed by matrix assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry (MS).…”
Section: Expression Of Lanthipeptides In Mammalian Cellsmentioning
confidence: 99%
“…Previous studies have demonstrated that introducing GluRS and tRNA Glu from the native lanthipeptide-producing organism could improve the production of fully modified peptides in E. coli. , Using this information, an improved production platform has been established for facile production of class I lanthipeptides in E. coli …”
Section: Introductionmentioning
confidence: 99%